POTENSI EKSPOR KOPI INDONESIA KE MALAYSIA - Zahirah, Ayu; Fadil, Cholid; Imaningsih, Niniek (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to identify factors that can influence Indonesian coffee exports to Malaysia. This study uses quantitative secondary data from 2015 to 2019, then is analyzed using the Error Correction Model (ECM). The independent variables used in this study are Malaysia's GDP, world coffee prices, Indonesian coffee prices, and the rupiah exchange rate against the US dollar, while the dependent variable is the amount of Indonesian coffee exports to Malaysia. The estimation results of multiple linear regression analysis show that the factors influencing Indonesian coffee exports to the Malaysian market are Indonesian coffee production, the price of Indonesian coffee exports to Malaysia and the exchange rate of the rupiah against the US dollar. whereas the RCA and CEPT AFTA mocks had no effect. From the results of the study it is known that Malaysia's GDP is not significant in the short and long term, but the world coffee market and Indonesian coffee prices do not have a significant effect in the short and long term, and the exchange rate has a significant short and long term effect on the volume of Indonesian coffee exports to Malaysia CEPT -AFTA. There is an opportunity to increase Indonesia's coffee exports to Malaysia, but in its development Indonesia's coffee exports to Malaysia have changed. The purpose of this research is to analyze the competitiveness and determinants of Indonesian coffee exports to Malaysia with the CEPT-AFTA system. The method used is Revealed Comparative Advantage (RCA) which analyzes the competitiveness of Indonesian coffee exports in the Malaysian market and the multiple linear regression method is used to analyze the factors affecting Indonesian coffee exports to Malaysia. The results of the RCA analysis show that Indonesian coffee has competitiveness (RCA score > 1). However, its competitiveness has decreased since the implementation of CEPTAFTA